PAHs in Chinese atmosphere Part I: Concentration, source and temperature dependence - Ma, Wan-Li; Liu, Li-Yan; Jia, Hong-Liang; Yang, Meng; Li, Yi-Fan (Atmospheric environment (1994), 2018)
The study on atmospheric polycyclic aromatic hydrocarbons (PAHs) in China has regional and global significance to understand the large scale atmospheric transport of PAHs. In this study, 16 US EPA priority PAHs were analyzed in more than 500 pairs of gas and particle phases samples, which were collected on the same schedule on a weekly basis from August 2008 to July 2009 at 11 urban sites (6 northern cities and 5 southern cities) across China. The average concentration was 239 ± 329 ng/m3 and 165 ± 164 ng/m3 for the northern cities and the southern cities, respectively. Different seasonal variations of atmospheric PAHs were observed between northern cities and southern cities, which were mainly caused by the different temperature effects in winter. Identified by principal component analysis, coal combustion and vehicle exhaust were the major sources of atmospheric PAHs in northern and southern cities of China, respectively. The temperature dependences of atmospheric PAHs were also different, which were caused by the different influences of temperature on identified sources. To our knowledge, this is the first comprehensive study to report the difference with concentrations, seasonal variations, sources and temperature dependences of atmospheric PAHs between northern cities and southern cities in China. [Display omitted] •More than 500 pairs of gas and particle phases were collected for PAHs analysis.•3-ring and 4-ring PAHs were the predominate homologues in atmosphere.•Significant difference between northern and southern cities was found in winter.•Coal combustion and vehicle exhaust were major sources of atmospheric PAHs.•Temperatures dependences of atmospheric PAHs were influenced by sources.